Static and Dynamic Balance Disorders in Patients With Rheumatoid Arthritis and Relationships With Lower Extremity Function and Deformities: A Prospective Controlled Study - Canan Şanal TOPRAK,; Mehmet Tuncay DURUÖZ,; Osman Hakan GÜNDÜZ, (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the static and dynamic balance disorders of patients with rheumatoid arthritis (RA) and to disclose the relationships with clinical, functional, and radiological findings of lower extremities. Patients and methods: A total of 81 patients with RA (15 males, 66 females; mean age 48.9±10.4 years; range 22 to 67 years) were compared with 84 age and sex-matched healthy controls (14 males, 70 females; mean age 45.9±12.1 years; range 24 to 70 years). Radiographic assessments of feet were performed to evaluate the presence of pes planus, hallux valgus, metatarsus primus varus, and splaying foot deformities. Foot functions of patients were determined with Foot and Ankle Outcome Score. The balance disorders of the subjects were evaluated with three static (modified clinical test of sensory interaction and balance, unilateral stance, weight bearing squat) and three dynamic (step-up-and-over, sit-to-stand, tandem walk) balance tests via the ‘Neurocom Balance Master’ device. Results: Rheumatoid arthritis patients had significantly higher sway velocity in unilateral stance and modified clinical test of sensory interaction and balance tests, higher step width and lower speed when walking on a line, lower rising index and higher movement time in step-up-and-over test compared to healthy controls (p<0.05). Performances on the sit-to-stand and weight bearing squat tests were comparable between both groups. Of the patients, although 61% had hallux valgus, 52% had metatarsus primus varus, 33% had pes planus, and 26% had splaying foot, these deformities were not correlated with Foot and Ankle Outcome Score or balance disorders. Presence of swollen joint was determined as the most relevant factor for balance disorders of RA patients. Conclusion: Patients with RA may have increased risk for balance disorders due to cumulative effect of the lower extremity impairments seen in the course of disease.